Al-Ghazali's Dhikr Theory: An Analysis of the Treatment of Psychological Problems in Islam - Jarman Arroisi; Ahmad Hisyam Syamil (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Modern human life is full of rapid development, mobility, and adjustment tendencies. Human life is filled with problems caused by various expectations that do not match reality. Dhikr is one of the therapies in psychology that helps individuals believe that all conflicts or life problems can be faced properly with the help of Allah SWT. This study aims to explore the theory of dhikr and analyze the treatment of psychological problems in Islam from the perspective of al-Ghazāli. The results of this study are da'wah therapy according to al-Ghazāli by using the descriptive-analytical method this study found several important conclusions. First, al-Ghazāli divides the principle of muāmalah in dhikr into four, namely, dhikr with the tongue, dhikr with the heart, dhikr with the secret, and dhikr with the spirit. Second, for al-Ghazāli Dhikr in addition to being a means of relationship between creatures and khāliq (creator) also contains high values and usability to be a solution to psychological problems that occur in humans. Third, Al-Ghazali in his psychotherapy in the treatment of psychological problems has applied treatment taken from Islamic law. Fourth, to improve psychological well-being and happiness, dhikr is needed because dhikr means that individuals always remember their God.